2018
DOI: 10.1039/c8nr02629g
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of Ag29(BDT)12(TPP)43− cluster: interactions of secondary ligands and their effect on solid state luminescence

Abstract: We present the first example of polymorphism (cubic & trigonal) in single crystals of an atomically precise monolayer protected cluster, Ag29(BDT)12(TPP)43-. We demonstrate that C-Hπ interactions of the secondary ligands (TPP) are dominant in a cubic lattice compared to a trigonal lattice, resulting in a greater rigidity of the structure, which in turn, results in a higher luminescence efficiency in it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
83
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(86 citation statements)
references
References 30 publications
3
83
0
Order By: Relevance
“…It has been demonstrated that the crystal of Ag 29 -Na 0 emitted at 670 or 700 nm with different crystalline patterns. 53 However, the emissions of Ag 29 -Na 1 and Ag 29 -Na 3 luminesced at 637 and 694 nm, respectively ( Fig. 2E; and see Fig.…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…It has been demonstrated that the crystal of Ag 29 -Na 0 emitted at 670 or 700 nm with different crystalline patterns. 53 However, the emissions of Ag 29 -Na 1 and Ag 29 -Na 3 luminesced at 637 and 694 nm, respectively ( Fig. 2E; and see Fig.…”
Section: Resultsmentioning
confidence: 89%
“…Although all types of Ag 29 nanoclusters (Ag 29 -Na 0 , Ag 29 -Na 1 , and Ag 29 -Na 3 ) presented cubic-like crystals at the macro-level (Fig. 2C,D, insets), 52,53 the emissions of them were entirely different. It has been demonstrated that the crystal of Ag 29 -Na 0 emitted at 670 or 700 nm with different crystalline patterns.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13] Ligands play a crucial role in the stabilization of nanoclusters. [14][15][16][17] The non-covalent interactions between surface ligands not only alter properties of clusters but also have signicant effects on nanocluster assembly and selfassembly. [18][19][20][21][22][23][24][25][26][27][28][29][30] For instance, Wu and co-workers demonstrated that C-H/p interactions facilitated the chiral arrangement of ligands, and the assembled ligands presented rotational and parallel patterns on the surface of the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%